Pemberian KIE Dengan Pengetahuan Ibu Nifas Mengenai Infeksi Masa Nifas Di Dusun Kelapa Dua - Dewi Susanti; Elen Parengkuan (Poltekkes Kemenkes Denpasar, 2020)
The puerperium begins after the placenta is born and ends when the uterus organs return to their pre-pregnancy state. The puerperium lasts about 6 weeks or 40 days but will recover completely within 3 months. The puerperium or postpartum period is also called puerperium which comes from the Latin word